Pengembangan Bahan Ajar Fisika pada Materi Listrik Searah Berbasis Keterampilan Proses Sains untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMA/MA Kelas XI - Duwi Nuvitalia; Eguh Endah Cayani; Siti Patonah; Ernawati Saptaningrum (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This study aims to develop teaching materials which then obtain the validity value of physics teaching materials on unidirectional electricity based on science process skills to improve critical thinking skills of high school / MA students in class XI. This research uses the R&D (Research and Development) method. The research stages include the potential and problem stages, data collection, product design, product validation and design revision. These results can be seen from the assessment of the validators as expert validation in the feasibility of teaching materials based on expert validation, based on the descriptions of the explanations of each chapter and the completion of the development of science process skills-based teaching materials to improve critical thinking skills. The validation results include content feasibility with a percentage of 83.6%, presentation feasibility 86.95%, language aspect 90%, science process skill aspect 91.65%, and critical thinking ability aspect 92.5%. The validation results are included in the very good category, so teaching materials based on science process skills for aspects of critical thinking skills are feasible to use.